2016
DOI: 10.5152/eurjrheum.2016.15074
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating disease activity in patients with ankylosing spondylitis and rheumatoid arthritis using 99mtc-glucosamine

Abstract: Objective: To evaluate the clinical utility of a novel radiotracer, Tc-glucosamine, in assessing disease activity of both rheumatoid arthritis (RA) and ankylosing spondylitis (AS).Material and Methods: Twenty-five patients with RA (nine males and 16 females) and 12 patients with AS (all male) at various stages of disease were recruited for the study. A clinical history and examination was performed, followed by the measurement of hematological, biochemical, and autoimmune serological parameters to assess disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The findings indicated that most of our participants had increased uptake of 99m Tc-ECDG in their clinically affected joints, with varying degrees of uptake. This is not different from the few studies that have used 99m Tc-ECDG to evaluate disease activity in patients with RA [ 6 , 14 ]. However, the level of agreement with the two modalities (clinical evaluation and 99m Tc-ECDG), expressed as percentages in the detection of synovitis in the knees, wrists, and hands, was 85, 75, and 56.2%, respectively.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The findings indicated that most of our participants had increased uptake of 99m Tc-ECDG in their clinically affected joints, with varying degrees of uptake. This is not different from the few studies that have used 99m Tc-ECDG to evaluate disease activity in patients with RA [ 6 , 14 ]. However, the level of agreement with the two modalities (clinical evaluation and 99m Tc-ECDG), expressed as percentages in the detection of synovitis in the knees, wrists, and hands, was 85, 75, and 56.2%, respectively.…”
Section: Discussionmentioning
confidence: 56%
“…However, these imaging modalities are not without their drawbacks. The major drawback of US is that it is operator-dependent and cumbersome, especially when almost every joint in both hands must be evaluated [ 4 , 6 ]. The inconvenience of this method is further increased if additional joints beside those in the hands need evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technetium-99 metastable ( 99m Tc) labeled glucosamine is a radiolabelled glucose analog that has been used for imaging active joint disease in patients with RA [7,8]. It offers an alternative to fluorine-18-fluorodeoxyglucose PET computed tomography ( 18 F-FDG PET/CT) imaging of patients with RA in facilities that do not have PET/CT machines.…”
Section: Introductionmentioning
confidence: 99%
“…4 We have radiolabelled GlcN with 99m-Technetium ( 99m Tc) and administered it intravenously to patients with varied rheumatic conditions including rheumatoid arthritis, ankylosing spondylitis and OA. 5 GlcN consumption was ceased 3-5 days prior to administration of this agent, to reduce any competitive inhibition of uptake.…”
mentioning
confidence: 99%